As contribuições de Paul Ricoeur à historiografia contemporânea - Rodrigo Bianchini Cracco (2015)
This dissertation seeks to research the appropriation of Paul Ricoeur’s philosophy by historians since the mid 1980s in an attempt to demonstrate how the historical and historiographic scenario of the late 20th century, characterized by the “crisis” of history, provides a favorable frame to renew the discipline. In this context, Ricoeur’s work offers forms to overcome, or to characterize with further details, the differences that make the current moment of historiography particular. Some central themes for history support this appropriation effort, with emphasis to the following: the role of narrative in historiography, the return of the subjects to the center of historiographic productions, the debate on the frontiers between memory and history, the history representation, especially the surpass of hegemonic explicative paradigms along the past century, majorly structuralism. For this purpose, we sought to present a general scenario of what is conventionally called “crisis” of the contemporary historiography, followed by a survey of the projects to reconstitute some of the areas of the discipline, with emphasis to Political History, History of Present Time, Cultural History, and New Social History. We also approached the historiographic “turnings” (Linguistics, critic, and hermeneutics) with attention to the debates developed by Ricoeur on such movements, and a special attention to the representative dimension of history. We also highlight how the current dialogue between history and philosophy implies a renewed interest of historians in the epistemological and ontological dimensions of history. We sought to direct the study of historiographic matters to Ricoeur’s philosophy highlighting the existing appropriations of his work by historians as well as the potential ones. The debates revealed that Ricoeur’s hermeneutics establishes a close dialogue with historiography issues and so provides theoretical and procedure references that are very fertile to historians. In addition, the articulation between explanation and understanding, deeply approached by Ricoeur, has direct effect on the tendency to the plurality of interpretation that characterized contemporary historiography.